Using benthic macroinvertebrates as indicators for assessment the water quality in River Nile, Egypt. Issue 1 (2nd January 2019) - Abdel Gawad, Soad Saad
ABSTRACT: Macrobenthic invertebrate's species are differently sensitive to a biotic and biotic parameters in their environment. So they are used as bioindicators of stat and water quality of aquatic environment. The main objective of this research is using benthic invertebrates for biological assessment of water quality. Twenty-three stations along River Nile from Aswan to Cairo were selected for sampling of benthic macroinvertebrates. Benthic fauna were collected seasonally by a Naturalist Rectangle Dredge with a net 500 µm mesh size. During the monitoring period (four seasons), forty taxa were identified. They belong to benthos sensitive individuals (25%) and medium tolerant benthos (10%) and tolerant benthos individuals (65%). Relations between macrobenthic communities and circumstances of aquatic ecosystem have been lately used to perform the Biological Monitoring Water Quality (BMWQ) score to evaluate quality level in River Nile water. The total BMWQ (T-BMWQ) score and the average BMWQ (A-BMWQ) score are calculated, and their relations with MacArther, Margalef, Menhinick diversity indices and family richness are also examined. BMWQ scores are more subtle measures to assess the response of macroinvertebrates to organic pollution than diversity indices and total population density. However, the A-BMWQ score is more sensitive to changes in family composition than the T-BMWQ score, whereas T-BMWQ score is more subtle to family richness and size of sample. A-BMWQ score is suggested for the biological evaluation of freshwater quality. Also Trent Biotic Index (TBI) was calculated in each station. All these biological indices examined in this study using benthic macroinvertebrates proved that some stations in Nile River were classified as good water quality, most of studied stations were moderate water quality and very few stations were classified as poor water quality.